Early‑onset neonatal sepsis and antibiotic use in Indonesia: a descriptive, cross‑sectional study - Salsabila, Khansa; Toha, Nadira Mohammad Ali; Rundjan, Lily; Pattanittum, Porjai; Sirikarn, Prapassara; Rohsiswatmo, Rinawati; Wandita, Setya; Hakimi, Mohammad; Lumbiganon, Pagakrong; Green, Sally; Turner, Tari (Springer, 2022)
Background: Early diagnosis and prompt antibiotic treatment are crucial to reducing morbidity and mortality of early-onset sepsis (EOS) in neonates. However, this strategy remains challenging due to non-specific clinical findings and limited facilities. Inappropriate antibiotics use is associated with ineffective therapy and adverse outcomes. This study aims to determine the characteristics of EOS and use of antibiotics in the neonatal-intensive care units(NICUs) in Indonesia, informing efforts to drive improvements in the prevention, diagnosis, and treatment of EOS. Methods: A descriptive study was conducted based on pre-intervention data of the South East Asia-Using Research for Change in Hospital-acquired Infection in Neonates project. Our study population consisted of neonates admit- ted within 72 h of life to the three participating NICUs. Neonates who presented with three or more clinical signs or laboratory results consistent with sepsis and who received antibiotics for 5 consecutive days were considered to have EOS. Culture-proven EOS was defined as positive blood or cerebrospinal fluid culture. Type and duration of antibiotics used were also documented. Results: Of 2,509 neonates, 242 cases were suspected of having EOS (9.6%) with culture-proven sepsis in 83 cases (5.0% of neonatal admissions in hospitals with culture facilities). The causative organisms were mostly gram-negative bacteria (85/94; 90.4%). Ampicillin / amoxicillin and amikacin were the most frequently prescribed antibiotics in hospi- tals with culture facilities, while a third-generation cephalosporin was mostly administered in hospital without culture facilities. The median durations of antibiotic therapy were 19 and 9 days in culture-proven and culture-negative EOS groups, respectively. Conclusions: The overall incidence of EOS and culture-proven EOS was high in Indonesia, with diverse and pro- longed use of antibiotics. Prospective antibiotic surveillance and stewardship interventions are required.